Body composition differences in patients with Metabolic Dysfunction-Associated Steatotic Liver Disease - Bernal-Contreras, Karen D.; Berrospe-Alfaro, Montserrat; de Cárdenas-Rojo, Regina López; Ramos-Ostos, Martha H.; Uribe, Misael; López-Méndez, Iván; Juárez-Hernández, Eva (Frontiers in Nutrition, 2024)
Background: Although body composition (BC) has been associated with Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD), there is little evidence of differences in BC in patients with MASLD regarding body mass index (BMI). The aim of this study was to determine differences in BC in terms of BMI and metabolic comorbidities in patients with MASLD. Material and Methods: It is a cross-sectional study with patients who attended the check-up unit. Liver steatosis was evaluated by controlled attenuation parameter, and patients were classified into five groups according to BMI, presence of MASLD, and metabolic characteristics: <25kg/m 2 non-MASLD; <25 kg/m 2 -MASLD; Overweight-MASLD; Metabolically Healthy Obese (MHO)-MASLD; and Metabolically Unhealthy Obese (MUO)-MASLD. BC was assessed by bioelectrical impedance and a Bioimpedance Vectorial Analysis (BIVA) was carried out. Differences in BC were analyzed by a One-Way ANOVA test. Univariate and multivariate analyses were performed for factors associated with abnormal BC. Results: A total of 316 patients were included. 59% (n =189) were male, with a mean age of 49 ± 10 years. Fat% significantly higher according to BMI was not different between BMI <25 kg/m 2 -MASLD and Overweight-MASLD groups. Skeletal muscle mass (SMM) was significantly lower in obesity groups with respect to overweight and normal weight groups. (p <0.05); however, no differences were observed in the post-hoc analysis. Extracellular Water/Intracellular Water ratio was significantly higher in the MHO-MASLD group and MUO-MASLD group compared with the BMI <25 kg/m 2 non-MASLD group and with the BMI <25 kg/m 2 -MASLD group. Abnormal Waist Circumference (WC) and liver steatosis were independent factors associated with abnormal BC. Conclusion: BC in MASLD patients varies according to BMI increase; changes could be explained by loss of SMM and not necessarily by the presence of metabolic abnormalities. High WC and the presence of steatosis are independent factors associated with altered BC.